Anticipated and Experienced Emotions in an Investment Experiment - Ronald Bosman; Frans van Winden (Tinbergen Institute, 2001)
This paper experimentally investigates investment behavior.We find that global risk – i.e. risk independent of an agent'sinvestment decision (like political risk) – substantiallydecreases investment. Also effort to obtain the capital usedfor investment decreases investment substantially. Theseresults are neither in line with expected utility theory norwith psychologically orientated theories of decision makingunder risk (e.g. prospect theory or regret theory). We discussthe economic relevance of the results and offer anexplanation that takes the role of experienced emotions(measured with self-reports) and anticipated emotions intoaccount. In addition, an (alternative) emotion-basedexplanation is provided for related experimental findingsconcerning the common ratio effect.
Keywords: 330; investment; global risk; effort; emotions; common ratio effect; Investition; Risiko; Test; Theorie; Investitionsklima; Emotion